Team Perceived Virtuality: Empirical Exploration of Its Two Dimensions - Costa, Patrícia; Handke, Lisa; König, Moana; Thieme, Olivia (Group Dynamics-Theory Research and Practice, 2023)
Objective: The present study aims at empirically exploring the construct of team perceived virtuality (TPV), validating its proposed bidimensional structure and predictive validity for affective and performance outcomes. Method: Three samples of 95 mix-gender, educated and Western teams, answered an online survey on team perceived virtuality (in form of collectively experienced distance and collectively experienced information deficits) teamwork engagement and team performance. Sample 1 consisted of 84 individuals, 63% female and 81%under 40 years of age. Sample 2 consisted of 68 individuals, 25% female and 64.2% under 40 years of age. Sample 3 consisted of 122 individuals, 53% female and 66% under 40 years of age. Results: The fit of a two-factor model (χ2 = 195.98, df = 20, p <.001, comparative fit index, CFI = 0.72, RMSEA = 0.18, SRMRwithin = 0.12) supported the bidimensional structure of the construct, and measurement invariance across samples was supported. Only distance is a significant predictor of teamwork engagement (β = −.50, p =.007); only information deficits (β=−.36, p=.076) are a significant marginal predictor of team performance; and both distance (β = −.33, p =.029) and information deficits (β = −.48, p =.002) are predictors of team adaptive performance, with the latter having a greater predictive power. Conclusions: This study provides evidence of team perceived virtuality as a team-level construct, validates its twofactor structure, and demonstrates the differential relationship between its two constituting dimensions and performance-related and affective-motivational outcomes, respectively. The generalizability of the findings is limited by samples’ characteristics.
CRIS-Team Scopus Importer:2023-09-18
Keywords: team perceived virtuality; team virtuality; virtual teams